Regime de Change et Croissance Economique : Une Investigation Empirique a Partir du Role de la Qualite Des Institutions (Global Journal of Human-Social Science, 2019)
The purpose of this work is to study the roleplayed by the quality of institutions in the growth performance and resilience to crises of the nature of the exchange rate regime. Based on data from 134 IMF member countries during the period 1984-2013 and based on IMF and Reinhart and Rogoff classifications. The results of the econometric estimations obtainedwith the less square generalized (LSG) methods show that, whatever the classification used, the quality of the institutions has a positive influence on the growth performance of the extreme exchange rate regimes (fixed and floating). However, it has been foundthat flexible exchange rate regimes are superior to fixed exchange rate regimes in terms of per capita real GDP growthusing the IMF classification. On the other hand, using the de facto classification of RR, itisrather the superiority of the fixed exchange rate regimesthat has been confirmed.
Keywords: exchange rate regime; GDP growth; quality of institutions